Capillary folding of patterned polymer polyhedra. (9th November 2020) - George, Derosh; Hernandez, Edwin A. Peraza; Madou, Marc J.
This paper presents a method to fabricate SU8 photopolymer and carbon polyhedral structures. First, patterned origami films with fewer cross-linked compliant folds and more cross-linked stiff faces are produced through differential UV exposure. The obtained patterned films are heated to increase their compliance by increasing polymer chain mobility. These softened films with designated compliant fold regions are then folded towards their target polyhedral shape using capillary forces induced by droplets deposited on top of them. The polyhedral shape of the folded films is locked in position by cooling them to room temperature and subsequently completing their cross-linking by an additional UV exposure step. The obtained polymer polyhedral structures can be converted into isometrically shrunken carbon structures through pyrolysis. This method for fabricating three-dimensional carbon polyhedra opens new ways to potentially fabricate complex structures of different material and surface properties through techniques such as electroplating and electroless deposition.